Critical soil moisture detection and water–energy limit shift attribution using satellite-based water and carbon fluxes over China - Y. Liu; J. Xiao; X. Li; Y. Li (Hydrology and Earth System Sciences)
Critical soil moisture (CSM), a tipping point of soil moisture (SM) at which surface fluxes shift from the energy-limited regime to the water-limited regime, is essential for the vegetation state and the corresponding land–atmosphere coupling. However, detecting CSM and attributing water–energy limit shifts to climate and ecosystem variables are challenging as in situ observations of water, carbon fluxes, and soil moisture (SM) are sparse. In this study, CSM was assessed over China using two satellite-based methods: (i) the difference between the correlation between SM and evapotranspiration (ET) and the correlation between vapor pressure deficit (VPD) and ET and (ii) the covariance between VPD and gross primary production (GPP). ET and GPP products were based on the Penman–Monteith–Leuning (PML) ET and GPP, Global LAnd Surface Satellite (GLASS) ET and GPP, Collocation-Analyzed Multi-source Ensembled Land Evapotranspiration (CAMELE) ET, Surface Energy Balance Algorithm for Land (SEBAL) ET, two-leaf light use efficiency (TL-LUE) GPP, and solar-induced chlorophyll fluorescence (SIF)-based (GOSIF) GPP. At flux sites, ET and GPP products were evaluated by eddy-covariance-based measurements; CSM values using two satellite-based methods were assessed using the soil moisture–evaporative fraction method. Their consistency at site scales demonstrated reliable results and applicability to regional scales. Through intercomparison, the spatial pattern of CSM from multi-source ET and GPP datasets was consistent and robust in eastern and southern China. Generally, CSM decreased from south to north. The Pearl River basin and Southeastern River basin displayed a relatively high CSM for clay-rich soils (e.g., 0.39 m3 m−3 using PML ET and 10 cm depth SM) and forests (e.g., 0.35 m3 m−3 using PML ET and 10 cm depth SM). Since CSM values were higher than the average SM at four soil layers, grassland and clay were water-limited. Thus, with increased water demand, western grasslands were more susceptible to water stress. These findings highlight the variability in CSM and the primary determinants of water–energy limit shifts, offering valuable insights into the potential water limitations on ecosystems under comparable SM circumstances.